PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA PENGEMBANGAN PRODUK BARU YANG DIMEDIASI OLEH INOVASI MODEL BISNIS (STUDI EMPIRIS PADA UMKM PASAR BERINGHARJO YOGYAKARTA) - Febnaufal R, Luthfi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research aims to explain the analysis of the influence of entrepreneurial orientation, new product development performance, and business model innovation through MSMEs at Beringharjo Market, Yogyakarta. In this increasingly dynamic and competitive era, they are faced with demands to create new innovative products, so that the business they run can grow and compete with other business competitors. The sample used in this research was 120 respondents. The sampling technique uses purposive sampling. The analysis technique used is SEM analysis and processed with the AMOS 24 application. The research results show that there is a positive and significant influence between entrepreneurial orientation, new product development performance and business model innovation.